Entrepreneurial Behaviour, Institutional Context and Performance of Micro and Small Livestock Enterprises in North Eastern Region of Kenya (Global Journal of Management and Business Research, 2016)
In this paper explores the relationship between entrepreneurial behaviour and firm performance from institutional environmental perspective More specifically the study argues that an economic process such as entrepreneurial behaviour is best understood from an institutional framework The assumption is that the motivation commitment experience knowledge and behaviours of the entrepreneur are core in the entrepreneurial process However firm performance is also dependent on the institutional and even the geographical context in which it operates It is on the basis of this logic that this paper argues that institutional parameters can moderate the way entrepreneurial behaviour influences performance of micro and small livestock enterprises in North Eastern Kenya
Keywords: entrepreneurial behaviour; institutions; firm performance; small and medium enterprises